Case Study of Young Adult Individual with Mild Depressive - Youza Diandra Putra Perkasa; Nanda Audia Vrisaba (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2025)
This study investigates the case of a 21-year-old female undergraduate student, referred to as TY, diagnosed with a Mild Depressive Episode (F32.0). The research employs a qualitative case study approach, utilizing semi-structured interviews, observations, and standardized measurement tools to explore the interplay of biological, psychological, and social factors contributing to TY's condition. Findings reveal a significant family history of mental disorders, including borderline personality disorder and bipolar disorder in her mother, which suggests a genetic predisposition to depression. Psychological stressors, such as familial conflicts and academic pressures, exacerbate her symptoms, characterized by persistent sadness, anxiety, and sleep disturbances. The results underscore the importance of the biopsychosocial model in understanding mild depression, emphasizing the need for integrated treatment plans that address genetic vulnerabilities, psychological dynamics, and social support systems. This case highlights the complexity of mental health disorders and the necessity for multifaceted approaches in clinical practice.